BIOECOLOGICAL STUDIES OF ANOAKTASAR SILKMOTH, ANTHERAEA FRITHII MOORE IN NORTH EAST INDIA - IBOTOMBISINGH, N.; DEBARAJ, Y; SOMENSINGH, L.; CHAOBASINGH, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Antheraea frithii Moore, an oak fed silk moth constitutes a part of the wild silk moth genetic diversity. Survey in the forest of North-East India records the availability of this wild silk moth in the oak growing areas of this region. In view of understanding the silk moth, the collection, conservation in ex-situ condition, bioecological parameters, characteristic features of the different stages and utilization of this particular silk moth were undertaken and presented in this paper. The silk moth behaves as bivoltine or trivoltine. Self coupling of moths occurs to the tune of 45 to 65% in captive condition inside spacious wire mesh cages (6' x 6' x 6.5"). The female moth lays 200250 eggs. Observation on the variations in morphological characters of the various developmental stages indicates the possibility of occurring natural hybridization among wild population. The study on the ex-situ conservation of this wild silk moth records the average values of the eight important parameters viz., fecundity, hatching percentage, cocoon yield, ERR96, cocoon weight, shell weight, shell ratio% and average single filament length during the three crops as 215-235 eggs, 65.22-75.00%, 40-50 cocoons/dfil, 26.66-32.00%, 4.52-4.60g, 0.51-0.55g, 11.25-11.96% and 625-665 m respectively. The present study opens a new vista for exploiting the particular wild silk moth for commercial production of tasar cocoons.